The relationship between IQ and performance on the MATRICS consensus cognitive battery - Christine Mohn; Kjetil Sundet; Bjørn Rishovd Rund (Schizophrenia Research: Cognition, 2014)
The associations between IQ and individual tests of neurocognitive function are well studied. However, there is a lack of information as to how IQ relates to performance on neuropsychological test batteries as a whole and in the same individuals. In this study, 250 healthy participants aged 20-69 years were tested with the Wechsler Abbreviated Scale of Intelligence (WASI) and the MATRICS Consensus Cognitive Battery (MCCB). In correlation analyses, IQ was significantly related to all MCCB scores, except the Social Cognition domain. Hierarchical regression analyses including gender, age, and education confirmed this association. For overall cognitive function, 50% of the variance was explained by IQ and demographic characteristics. For the domains Speed of Processing, Working Memory, Visual and Verbal Learning, IQ explained a larger proportion of the variance than the demographic factors did. The implication is that these domains may provide information of a person’s intelligence level.